THE INFLUENCE OF MOTIVATION, COMPENSATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT THE HORISON BANDUNG HOTEL - Akbar, Ridho Riadi; Maisan, Kifa (Universitas Indonesia Membangun (Inaba), 2022)
The purpose of this study was to determine the effect of Motivation, Compensation and Organizational culture on employee performance. The research method uses quantitative methods with descriptive and verification approaches. Data collection techniques were obtained through interview, questioner, study literature and access to the website. Populations in this study have as many as 114 employees. The research sampling technique was simple random sampling with a total sample of 54 employees. Data analysis in this study used descriptive analysis, Classical assumption test, Multiple linear regression analysis, Correlation coefficient analysis, Coefficient of determination (R2) and hypothesis testing with t test and F test with the help of the SPSS Program. Based on the results of the study, it is known that there is a partially significant positive influence on motivation, compensation and organizational culture on employee performance. Based on the limitations of the research at Hotel Horison Ultima Bandung and related to other 4-star hotels, the research does not show KPI hotel employees only get data from the results of questionnaires and interviews. The research contribution for Hotel Horison Ultima Bandung as the object of research, for Universitas INABA Research, and especially in the field of Human Resource Management. The novelty that this research can produce is to see the influence of motivation, compensation, and work culture, especially with the object of research at Hotel Horison Ultima Bandung.